Effect of Securigera securidaca Seeds on Blood Glucose Level of Normal and Diabetic Rats: Antidiabetic effect of S. securidaca - Minaiyan, Mohsen; Moattar, Fariborz; Vali, Azadeh (Iranian Journal of Pharmaceutical Sciences, 2006)
The search for indigenous natural antidiabetic agents is still ongoing. Securigera securidaca seeds are reputed in folk medicine for their value as an antidiabetic remedy, so the present study was carried out to investigate the hypoglycemic efficacy in both normal and streptozotocine (STZ)-induced diabetic rats. Hydroalcoholic extract of the seeds were administered orally with doses of 200, 400, and 800 mg/kg and intraperitoneally with a dose of 400 mg/kg to separated groups of male Wistar rats. The control and reference groups received oral vehicle (1 ml/kg) and glibenclamide (10 mg/kg, p.o.), respectively. Blood samples were collected at 0, 1, 2, 3, 4, and 8 h after treatment and blood glucose levels were determined using glucose oxidase method. Results indicated that hydroalcoholic extract of S. securidaca was not effective to lower blood glucose level both in normal and diabetic rats. Glibenclamide on the other hand, reduced blood level of glucose in diabetic rats and caused hypoglycemia in normal animals and the effect was time-dependent. It is concluded that seeds of S. securidaca were not effective to reduce blood glucose level in this animal model of diabetes.